1999
DOI: 10.1007/s004030050442
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes and altered keratinocytes express interferon-γ and interleukin 6 in lichen planus

Abstract: Lichen planus is assumed to represent a delayed hypersensitivity reaction, in the course of which cytokines control the proliferation and differentiation of cytotoxic T lymphocytes which attack the epidermis and cause apoptosis of undifferentiated keratinocytes. Since interferon-gamma and interleukin 6 are known to be markedly generated in lichen planus, we investigated the cellular localization of these cytokines in affected skin/oral mucosa biopsy specimens using in situ hybridization for interferon-gamma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 31 publications
6
46
1
2
Order By: Relevance
“…Fayyazi et al observed the expression of IFN-γ mRNA and interleukin 6 mRNA in the basal and suprabasal keratinocytes of altered skin/oral mucosa [35]. Simark-Mattsson et al found that there were cells expressing mRNA for IL-2, IL-4, IL-10, TNF-α and TGF-β1 in all OLP lesions.…”
Section: Discussionmentioning
confidence: 97%
“…Fayyazi et al observed the expression of IFN-γ mRNA and interleukin 6 mRNA in the basal and suprabasal keratinocytes of altered skin/oral mucosa [35]. Simark-Mattsson et al found that there were cells expressing mRNA for IL-2, IL-4, IL-10, TNF-α and TGF-β1 in all OLP lesions.…”
Section: Discussionmentioning
confidence: 97%
“…They also demonstrated that proinflammatory cytokines such as IFN-γ and IL-6 were produced not only in active T lymphocytes but also in keratinocytes in basal and suprabasal layers [28]. They reported that TNF-α and IFN-γ may lead to liquefaction degeneration in basal membrane and basal keratinocytes.…”
Section: Discussionmentioning
confidence: 96%
“…Gu et al [4] detected elevated levels of oral and serum IL-6 in patients with ulcerative lichen in comparison to the reticular lichen and controls thus suggesting that elevated IL-6 might reflect chronic inflammatory nature of ulcerative lichen. On the contrary, Fayyazi et al [5] suggested that OLP is a delayed type of hypersensitivity reaction in which cytokines (including IL-6) control proliferation and differentiation of cytotoxic Tlymphocytes which attack epidermis and lead to apoptosis of undifferentiated keratinocytes. Last but not least Rhodus et al [6] reported that patients with oral squamous cell carcinoma have elevated salivary IL-6 and TNF-α in comparison to the patients with precancerous lesions and healthy controls.…”
Section: Editorialmentioning
confidence: 99%